The Time of Montage - de Naverán, Isabel; Vergara, Leire (Re-visiones, 2024)
In this lecture-conversation, Isabel de Naverán and Leire Vergara offer an array of readings, life experiences and descriptions of films in order to address the concept of montage as applied to contemporary choreography and curatorial work. Taking the description of several scenes as a point of departure, the authors propose an understanding of montage (both in exhibits and in choreography) based on a specific temporality in which peripheral elements and everyday life lend intention and meaning to the work. In this partially scripted conversation the authors exchange their perspectives on the white cube and the black box, and question some of the dynamics of those two mechanisms. The Time of Montage has been staged on three occasions. The first was in the Teatro Pradillo in Madrid, in the context of Laboratorio 987 (2013) organized by Chus Domínguez, Nilo Gallego and Silvia Zayas and the cycle of exhibits Form and Vouloir-dire curated by Leire Vergara in 2012 at the MUSAC (Museum of Contemporary Art of Castille and Leon), the second was in the Laboratorio 987 at MUSAC within the same initiative, and the third time in Sukaldea-Tabakalera in San Sebastián (2014) as part of the program Paracinema curated by Esperanza Collado. Each staging involved some changes to the text, the props and the dialogue conducted afterwards. RE-VISIONES presents a new version of the lecture, including the transcription and translation into English of the first two points proposed by each author, and a video recording of the lecture as staged at the Teatro Pradillo.